2020
DOI: 10.3390/s21010034
|View full text |Cite
|
Sign up to set email alerts
|

Optical Designs with Curved Detectors for Fiber Bragg Grating Interrogation Monitors

Abstract: In this paper, we evaluate the application of curved detectors and freeform optics technologies for fiber Bragg gratings (FBGs) interrogation monitors design. It is shown that, in a high-dispersion spectrograph scheme, the camera part operates in special conditions, which result in a field curvature change. This field curvature can be compensated by the use of a curved detector. When used together with freeform optics, the curved detectors allow for reduction of the number of optical components to two or even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In [10], E. Muslimov et al evaluated the application of curved detectors and freeform optics technologies for the design of FBG interrogation monitors. It was shown that in a high-dispersion spectrograph scheme, the camera part operates in special conditions, which results in a field curvature change.…”
Section: Original Interrogatorsmentioning
confidence: 99%
“…In [10], E. Muslimov et al evaluated the application of curved detectors and freeform optics technologies for the design of FBG interrogation monitors. It was shown that in a high-dispersion spectrograph scheme, the camera part operates in special conditions, which results in a field curvature change.…”
Section: Original Interrogatorsmentioning
confidence: 99%